ANALISIS LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KOMITMEN ORGANISASIONAL DENGAN KEPUASAN KERJA SEBAGAI VARIABLE INTERVENING (STUDI KASUS PADA PT SEJATI KARYA PERKASA MEDAN ) - Anton, Anton; Karo-karo, Alex P.; Widjaja, Dennis; Rezeki, Rezeki; Martinus, Martinus (Jurnal Manajemen dan Bisnis, 2023)
This study aims to understand the Work Environment and Organizational Culture on Organizational Commitment with Job Satisfaction as an intervening variable. There are many causes of job dissatisfaction, therefore this is very related because if employees experience dissatisfaction it will have an impact on increasing high turnover, which means that employees become disloyal to the organization related to organizational commitment. Sometimes simple things are not paid attention to, such as an uncomfortable work environment and organizational culture, reliable human resources can resign. One important factor within the company is managing human resources so that they can utilize them to optimize the achievement of the company's vision. This study used a sample of 100 employees at PT Sejati Karya Perkasa Medan which were processed using SPSS with path analysis statistics and the results showed that there was a positive and significant influence between work environment and organizational culture, job satisfaction and organizational commitment.